"Showing respect" in Bible translation - R. van der Spuy (Acta Theologica)
This article focuses on the way respect is shown by using 2nd person personal pronouns in languages that distinguish between you plural (you all), you honorific (polite) and you singular (familiar) forms. It discusses the likely influence of the well known Russian Synodal Translation on other translations in the former Soviet Union regarding the usage of the 2nd person personal pronouns. This article also highlights by way of comparison how Afrikaans and other Western translations use the 2nd person personal pronoun. Problems often arise when the original languages are followed too literally without taking into account the target culture, or due to the translators’ perception of the social status of the engaging referents. Issues discussed and principles drawn from this study not only apply to the Russian world, but also influence all translations that have a set of 2nd person personal pronouns that distinguishes between 2nd person singular, plural and polite forms.